The Influence of Perceived Ease of Use, Electronic Word of Mouth (E-WOM), Price and Service Quality on Consumer Satisfaction for Grab Online Transportation Users - Putri Nabila, Afita; Violinda, Qristin; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The study aims to test and analyze the influence of perceived ease of use, electronic word of mouth, price, and service quality on consumer satisfaction in Grab online transportation in Semarang City. This type of research is quantitative research. The population in this study were consumers who had used Grab online transportation services in Semarang City with a sample of 96 respondents. The data collection technique was through a questionnaire in the form of a google form, then the data was processed through the IBM SPSS Statistics version 26 application with multiple linear regression analysis. This study resulted in that perceived ease of use had no effect on consumer satisfaction, electronic word of mouth had a positive and significant effect on consumer satisfaction, price had a positive and significant effect on consumer satisfaction and service quality had a positive and significant effect on consumer satisfaction. Based on the results of the determination coefficient R test with an Adjusted R Square value of 0.630 or 63%.